2015
DOI: 10.1007/s00344-015-9544-3
|View full text |Cite
|
Sign up to set email alerts
|

From Facts and False Routes: How Plant Hormone Research Developed

Abstract: Our understanding of how plant hormones work has tremendously increased over the last decades. However, such progress was not possible without those who laid the foundation of the work which was sometimes much more tedious in early days than today. Therefore, we thought it timely to follow-up on historical aspects of plant hormone research. The development in the field of auxins, cytokinins, gibberellins, abscisic acid, jasmonates, brassinosteroids, and ethylene are accompanied with personal recollections. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Nitric oxide (NO) is a widely known nitrogen oxide and free radical gas, which was first identified as a unique diffusible molecular messenger and the endothelial relaxing factor in animals. , As early as 1992, NO was recognized as one of the most critical plant signals that regulates cell death and defense under biotic and abiotic stresses in plants. , In this study, we classify nitric oxide as a plant hormone based on previous research and its physiological role in plants, ,, which is consistent with the definition of plant hormones …”
Section: Effects Of Phytohormones On Animalssupporting
confidence: 59%
See 2 more Smart Citations
“…Nitric oxide (NO) is a widely known nitrogen oxide and free radical gas, which was first identified as a unique diffusible molecular messenger and the endothelial relaxing factor in animals. , As early as 1992, NO was recognized as one of the most critical plant signals that regulates cell death and defense under biotic and abiotic stresses in plants. , In this study, we classify nitric oxide as a plant hormone based on previous research and its physiological role in plants, ,, which is consistent with the definition of plant hormones …”
Section: Effects Of Phytohormones On Animalssupporting
confidence: 59%
“…In this study, we reviewed the physiological effects of phytohormones in animals regulated by phytohormones. We determined whether a substance is a plant hormone by the revealed evidence for its biosynthesis, degradation, conjugation, transport, receptor(s), signal transduction, and physiological effect(s). , Our review demonstrated that the consumption of phytohormones is a double-edged sword. Excessive use of these can lead to possible food safety issues.…”
Section: Effects Of Phytohormones On Animalsmentioning
confidence: 99%
See 1 more Smart Citation